NILAI BUDAYA DALAM DONGENG BAKUMPAI (CULTURAL VALUES IN BAKUMPAI FOLKTALE) - Mahmudi Mahmudi (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2013)
AbstractCultural Values in Bakumpai Folktale. Folktale as one of oral literary which containeducative advice for the next generation. Folktale are imaginative or vicarious andfantasy stories in which the events do not really take place. The events which are notifiedin the story tend to be behavior/moral lessons. This research is aimed at obtainingobjective description about three cultural values and Bakumpai folktales: (1) culturalvalues about human life, (2) cultural values about human’s viewpoints to the nature, (3)cultural values about human relationship one another. The theory used as basic ofinstrument development is oral literary theory and narratives Aarne and Stith Thomson,James Danandjaja, and the theory about C. Klucklohn cultural values. Data of thisresearch is Bakumpai folktales which consist of 11 (eleven) folktales. The approachesused in this research are qualitative and sociology research, descriptive method andcontent analysis technique. The primary instrument is the researcher. The secondaryinstruments are the informants, Bakumpai folktales, tape recorder, cell phones andresearch notes. The data analysis is done during the collecting of data. The researchresults shows that there are three cultural values in Bakumpai folktales, those are culturalvalues of human life (55 items), cultural values about human’s viewpoints to the nature(24 items), cultural values about human relationship one another (31 items). The mostdominant values about human relationship one another, especially in making a livingto meet daily needs.Keywords: cultural value, bakumpai, folktaleAbstrakNilai budaya dalam Dongeng Bakumpai. Dongeng sebagai salah satu sastra lisanyang berisi saran edukatif untuk generasi berikutnya. Dongeng adalah cerita imajinatifatau perwakilan dan fantasi di mana peristiwa tidak benar-benar terjadi. Peristiwayang diberitahukan dalam cerita cenderung perilaku/pelajaran moral. Penelitian inibertujuan untuk mendapatkan gambaran obyektif tentang tiga nilai-nilai budaya dalamdongeng Bakumpai: (1) nilai-nilai budaya tentang kehidupan manusia, (2) nilai-nilaibudaya tentang sudut pandang manusia terhadap alam, (3) nilai-nilai budaya tentanghubungan manusia satu sama lain. Teori yang digunakan sebagai dasar pengembanganinstrumen adalah teori sastra lisan dan narasi Aarne dan Stith Thompson, JamesDanandjaja, dan teori tentang nilai-nilai C. Kluckholn budaya. Data dari penelitianini adalah dongeng Bakumpai yang terdiri atas 11 (sebelas) dongeng. Pendekatanyang digunakan dalam penelitian ini adalah kualitatif dan penelitian sosiologi, metodedeskriptif dan teknik analisis isi. Instrumen utama adalah peneliti. Instrumen sekunderadalah informan, dongeng Bakumpai, tape recorder, ponsel dan catatan penelitian.Analisis data dilakukan selama pengumpulan data. Hasil penelitian menunjukkan bahwaada tiga nilai-nilai budaya dalam dongeng Bakumpai, yaitu nilai-nilai budaya dari62kehidupan manusia (55 item), nilai-nilai budaya tentang sudut pandang manusiaterhadap alam (24 item), nilai-nilai budaya tentang hubungan daya manusia satu samalain (31 item). Yang paling dominan nilai-nilai tentang hubungan manusia satu samalain, terutama dalam mencari nafkah untuk memenuhi kebutuhan sehari-hari.Kata-kata kunci: nilai budaya, bakumpai, dongeng